On-demand software licence provisioning in grid and cloud computing. (1st January 2013) - Raekow, Yona; Simmendinger, Christian; Jenz, Domenic; Grabowski, Piotr
The lack of licence management schemes in distributed environments is becoming a major obstacle for the commercial adoption of grid or cloud infrastructures. In this paper, we present a complete licence management architecture that enables a pay-per-use licence management, which can be deployed together with an on-demand computing scenario. Our architecture enables authenticated access to a remote licence server. The licence management architecture can be deployed in any distributed environment. It supports existing client/serverbased software licence management tools (e.g. FlexNet Publisher). This allows an easy transition from current software licence business models, which support only a local licence management towards business models that support licence management in distributed environments.